Synergistic Antioxidant Activity of Lycium barbarum Polysaccharide and Chlorogenic Acid and Its Effect on Inflammatory Response of NR8383 Cells - Junye Yin; Dandan Zhao; Jian Song; Ran Gao; Xuan Wang; Huan Rao; Xiaoguang Gao; Jianxiong Hao (Foods)
It is inevitable for polyphenols and polysaccharides to interact during food preparation. Modifications in microstructure can lead to changes in the physical and chemical properties of food systems, which in turn may influence the nutritional characteristics and functional activities of the food. Recent studies have shown that, in addition to traditional Chinese medicine compounds, certain natural polysaccharides and polyphenols exhibit significant anti-inflammatory and antioxidant properties. These compounds are also associated with beneficial therapeutic effects for the prevention and treatment of acute lung injury. The objective of this study was to examine the synergistic antioxidant effects of chlorogenic acid (CA) and Lycium barbarum polysaccharide (LBP) in various ratios, along with their combined antioxidant and anti-inflammatory effects on LPS-induced inflammation in rat alveolar macrophages. Using the Combination Index (CI), which quantifies the synergistic or antagonistic effect of two substances, all four combinations showed synergistic antioxidant properties over a range of concentrations by in vitro antioxidant property experiments. However, based on comparing them, the four group ratios exhibited the highest antioxidant activity of the infusion at CA:LBP = 1:7, indicating synergistic interactions (CI < 1). In addition, the antioxidant and anti-inflammatory effects of the CA-LBP complex were observed to alleviate cellular inflammatory injury by reducing LPS-induced nitric oxide and reactive oxygen species production and inhibiting the release of inflammatory factors such as TNF-α and IL-6.